(untitled) (Global Journal of Human-Social Science, 2019)
In this paper we discuss the positive heuristic potential of two Brazilian discourse theories the first one is Semiotics of the song by the Brazilian researcher Luiz Tatit the second one is the Theory of basic stereotypes and opposed stereotypes by the Brazilian researcher S rio Possenti The first theory on one hand is based on the preparation of a complete concept for a systematic study of Brazilian songs considering the meeting of melody and lyrics The Semiotics of the Song Theory presents an isotopic analysis of elements of content and expression in which melody and lyrics are taken as equivalent structural elements The researcher Tatit in his studies relates aspects of expression to aspects of content in various Brazilian popular songs He comprehends that Brazilian songs may be assigned to three major types thematized passionalized and figuretivized